Project Based Learning pada Materi Bahaya Miras, Judi dan Pertengkaran: (Studi dalam Mata Pelajaran Pendidikan Agama Islam) - Tutik Haryanti (GHIROH, 2022)
This article focuses on the application of the Project Based Learning model in PAI learning. This study aims to investigate the extent to which junior high school students in Bintan Regency can improve their learning outcomes in PAI learning about the dangers of alcohol, gambling and fighting. To answer this question, this study uses classroom action research. The research participants were 20 first semester students of Junior High School in Bintan Regency, Riau Islands. This research lasted for three months in which students were given actions in the form of pretest and posttest. The results of data analysis showed that students had learning outcomes that did not meet the KKM for PAI learning about the dangers of alcohol, gambling and fighting before being given action, but showed an increase in learning outcomes after experiencing the action. This study offers pedagogical implications and suggestions for future researchers.